In situ Electron Microscopy of Complex Biological and Nanoscale Systems: Challenges and Opportunities - Han, Zexiang; Porter, Alexandra E. (Frontiers in Nanotechnology, 2020)
In situ imaging for direct visualization is important for physical and biological sciences. Research endeavors into elucidating dynamic biological and nanoscale phenomena frequently necessitate in situ and time-resolved imaging. In situ liquid cell electron microscopy (LC-EM) can overcome certain limitations of conventional electron microscopies and offer great promise. This review aims to examine the status-quo and practical challenges of in situ LC-EM and its applications, and to offer insights into a novel correlative technique termed microfluidic liquid cell electron microscopy. We conclude by suggesting a few research ideas adopting microfluidic LC-EM for in situ imaging of biological and nanoscale systems.